Physiological quality of soybean seeds treated with different spray volumes - Segalin,Samantha Rigo (2013)
The aim of this study was to define the influence of treatments with different seed spray volumes and their effects on the physical and physiological quality. The soybean seeds from cultivars NA 5909 RG and BMX Potência RR were used and three lots of each cultivar were selected in sieves of different diameters (5.5; 6.0 and 6.5 mm). The treatments consisted of different seed volumes: 1) non-treated seeds; 2) 600 mL.100 kg of seeds-1; 3) 800 mL.100 kg of seeds-1; 4) 1000 mL.100 kg of seeds-1; 5) 1200 mL.100 kg of seeds-1; 6) 1400 mL.100 kg of seeds-1. The physical parameters evaluated were mechanical damage, water content and variations in the length and width of the seeds. The physiological seed quality was determined by germination, first count germination, length and dry weight of seedlings, field emergence and emergence speed index tests. In terms of use of the product in liquid form, it is possible to use the treatment in spray volumes up to 1400 mL.100 kg seed-1, regardless the cultivar or seed size and without damaging the soybean seeds physically and physiologically.